2010
DOI: 10.1007/s12595-010-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors inducing aestivation of the giant African land snail Achatina fulica Bowdich (Gastropoda: Achatinidae)

Abstract: The giant African land snails Achatina fulica Bowdich occurring in Kolkata, West Bengal, India undergo aestivation with the advent of adverse conditions by the end of October or early part of November, each year. Experiments were conducted to study the factors inducing aestivation in these snails. It is revealed that the type of plant-foods, the length of starvation, the degrees of temperature and the percentages of relative humidity are the factors inducing aestivation in A. fulica of course, just at the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Terrestrial invasive gastropods like Lissachatina fulica prefer high humidity conditions for growth and thus their activity is restricted to the periods of ISM or southwest monsoon, when temperatures are typically in the range of 15–28°C (Rahman & Raut, ). Higher rainfall amounts (>50 mm/week) are always associated with higher ambient humidity and can act as triggers to successfully terminate aestivation in L. fulica .…”
Section: Resultsmentioning
confidence: 99%
“…Terrestrial invasive gastropods like Lissachatina fulica prefer high humidity conditions for growth and thus their activity is restricted to the periods of ISM or southwest monsoon, when temperatures are typically in the range of 15–28°C (Rahman & Raut, ). Higher rainfall amounts (>50 mm/week) are always associated with higher ambient humidity and can act as triggers to successfully terminate aestivation in L. fulica .…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the type of plant foods, the length of starvation, the degree of temperature, and percentage of relative humidity are the factors that induce estivation. In estivation state, snails overcome the unfavorable conditions by adjusting their physiological conditions (Rehman and Raut ). To our knowledge, a detail survey of culturable and uncultured bacteria in the whole GI tract of this snail has not been carried out so far.…”
Section: Introductionmentioning
confidence: 99%
“…It is appear from our results that the emergence of the aestivated snails is strongly influenced by the changes of temperature (aestivated snails were more active at temperature 25 0 C and became less active with increasing temperature), that trigger the genetic process and induce aestivation in snails (Rahman and Raut, 2010).This finding is in accordance with that obtained by Ali and Suleman,( 1992) who assured that in Pakistan both the adult and immature stages snails of M.obstructa were more active during wet days of spring months where the prevailing temperatures were around 25 0 C and become inactive during the summer months and they either died or aestivated, as large numbers of empty shells and dormant snails were observed.…”
Section: -The Effect Of Temperatures On Food Consumption Of Juvenile and Adult Stages Of M Cartusianamentioning
confidence: 66%